Antimicrobial utilization in Hajj 2022: An evaluation of quality indicators - Abrar K. Thabit; Nawal Alfardus; Khalid Eljaaly; Mohammed Alshennawi (Elsevier, 2024)
Background: The mass gathering in Hajj (Islamic pilgrimage) makes the spread of infectious diseases inevitable. Antibiotics are frequently prescribed during this season. We aimed to measure antimicrobial utilization during the 2022 Hajj and evaluate the practice using quality indicators. Methods: Antimicrobial utilization by Hajj medical facilities (77 primary clinics and 7 hospitals) was measured using the anatomic therapeutic classification defined daily dose (DDD) and DDD/1,000-inhabitant/day (DID), where inhabitants were the Hajj 2022 pilgrims (n = 899,353). Quality indicators included percentages of consumption of different antibiotic classes of the total consumption of antibacterials for systemic use in DID. Results: During Hajj, there was 87,173 outpatient visits and 740 hospitalizations (215 critically ill). Amoxicillin was the most prescribed antibiotic (DID=11.708) followed by azithromycin (DID=7.395). Penicillins fell in the second quartile (i.e., highly prescribed) with a quality indicator value (J01_CE%) of 48.149. The consumption of other antibacterials, including fluoroquinolones, fell in the first quartile (<25%). The overall ratio of broad- to narrow-spectrum antibiotic prescribing (J01_B/N) was 1.49. Conclusion: Although the prescribing of β-lactams over fluoroquinolones indicates a good practice, clinicians should be reminded that most infections spreading in mass gatherings are viral; hence, do not require antibiotics. Implementation of antimicrobial stewardship is recommended to improve antimicrobial utilization.